A study of leadership and implementing a regional trauma care network in the East Midlands - Lees-Manning, Edward M. (2016)
This dissertation focuses on issues of innovation and leadership in healthcare. It examines these issues in the context of the reorganisation of trauma care services in the East Midlands into a regionalised trauma network. It is a qualitative study using a general inductive theoretical approach to examine interview data from a sample of 6 members of the network as they discuss issues of management and leadership.